The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12889-023-15876-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to promote HPV vaccination globally

Abstract: Background Despite the human papillomavirus (HPV) vaccine being a safe, effective cancer prevention method, its uptake is suboptimal in the United States (U.S.). Previous research has found a variety of intervention strategies (environmental and behavioral) to increase its uptake. The purpose of the study is to systematically review the literature on interventions that promote HPV vaccination from 2015 to 2020. Methods We updated a systematic revie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…Using the P3 Model in our study and the subsequent findings, allowed for consideration of multi-level interventions for increasing HPV vaccination. Research has shown numerous programs that promote HPV vaccination operate at a single level [ 59 ]. Mostly focusing on either the patient or provider levels and a lack of focus on including facilitators and barriers at the practice level [ 60 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the P3 Model in our study and the subsequent findings, allowed for consideration of multi-level interventions for increasing HPV vaccination. Research has shown numerous programs that promote HPV vaccination operate at a single level [ 59 ]. Mostly focusing on either the patient or provider levels and a lack of focus on including facilitators and barriers at the practice level [ 60 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…125 Several reviews have found multilevel approaches effective when targeting parent psychosocial factors (knowledge, beliefs, outcome expectations, intentions, using informational text included with reminders) and behaviors, clinician recommendation, and patient-targeted and provider-targeted clinic systems (e.g., dashboards and reminder systems). [126][127][128][129][130][131] State-wide policy interventions (including formalized requirements and school mandates) have been few. Community-based interventions to increase uptake via partnerships, involving community health workers, have shown promise.…”
Section: Hpv Vaccinationmentioning
confidence: 99%
“…Many of these multilevel approaches have targeted racially and ethnically minoritized populations to address health disparities. [119][120][121][122][123][124][125][126][127][128][129][130]132,133…”
Section: Hpv Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, too few interventions have included a multilevel approach, despite research showing its effectiveness, or indeed have reported their effect on VC. 19 The PrevHPV research program was launched in 2018 to improve HPV acceptability and VC in France. It used the Integrated Behavior Change Model as the theoretical background.…”
Section: Introductionmentioning
confidence: 99%